Transport Phenomena of Darcy-Forchheimer Eyring-Powell Nanofluid Flow with Cattaneo-Christov Dual Flux Across a Riga Plate - Ali, Asif; Aslam, Muhammad Nauman; Junaid, Muhammad Sheraz; Basit, Abdul; Nisa, Mehr un (Journal of Applied Nonlinear Dynamics, 2026)
This research investigates the Darcy-Forchheimer flow of a non-Newtonian Eyring-Powell nanofluid containing copper nanoparticles. The physical configuration for the mathematical model is based on the Riga plate. The heat transfer rate of the fluid model is enhanced by utilizing the Cattaneo-Christov model in combination with the heat and mass equations. The system of partial differential equations governing the flow is converted into a system of ordinary differential equations through similarity transformations. The MATLAB bvp4c technique is employed to obtain numerical solutions, while the Homotopy analysis method is utilized to derive analytical solutions. The results of numerical and analytical methods are compared in tabular form. The graphical results of various physical quantities with different parameters are presented. It has been observed that the higher radiation and heat generation parameters increase the temperature of the fluid. The concentration profile is enhanced with the greater chemical reaction parameter and Schmidt number. As the temperature distribution parameter increases, the skin friction coefficient increases, while the Nusselt number and Sherwood number decline with the greater radiation parameter and the chemical reaction parameter, respectively. The Nusselt number increases when the heat absorption parameter varies from 0.0 to 6.0, and a decline in the Sherwood number is observed as the Schmidt number varies from 0.0 to 0.6 for Eyring-Powell fluids.